The Interacting Axes of Environmental, Health, and Social Justice Cumulative Impacts: A Case Study of the Blueberry River First Nations - Maya Gislason; Holly Andersen (Healthcare, 2016)
We consider the case of intensive resource extractive projects in the Blueberry River First Nations in Northern British Columbia, Canada, as a case study. Drawing on the parallels between concepts of cumulative environmental and cumulative health impacts, we highlight three axes along which to gauge the effects of intensive extraction projects. These are environmental, health, and social justice axes. Using an intersectional analysis highlights the way in which using individual indicators to measure impact, rather than considering cumulative effects, hides the full extent by which the affected First Nations communities are impacted by intensive extraction projects. We use the case study to contemplate several mechanisms at the intersection of these axes whereby the negative effects of each not only add but also amplify through their interactions. For example, direct impact along the environmental axis indirectly amplifies other health and social justice impacts separately from the direct impacts on those axes. We conclude there is significant work still to be done to use cumulative indicators to study the impacts of extractive industry projects—like liquefied natural gas—on peoples, environments, and health.